Legal and Ethical Issues in the Constitutional Court Decision Concerning Minimum Age Limits for Presidential and Vice Presidential Candidates - Prasetyo, Yogi; Indiantoro, Alfalachu; Isnandar, Aries (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2024)
This article aims to explain the basic considerations of Constitutional Court Judges in deciding case Number.90/PUU-XXI/2023 and analyze the existence of controversial issues in this decision. The background to this writing is a decision by the Constitutional Court which is considered unusual. There are new things out of the ordinary in deciding cases and the momentum approaching the 2024 general election has become a sensitive and interesting study. The research method used in this writing is a normative juridical method with a legal philosophy approach. This is in accordance with the main problem of analyzing the judge’s decision from a philosophical perspective. Material in the form of library data in the form of statutory regulations and scientific works related to the research theme. The results of the research show that there are several basic reasons for judges in deciding this case, such as political rights and the time for the general election which is getting closer. Apart from that, the decision of the Constitutional Court contains ethical issues in it, because in the formation process it was carried out by judges who had been legally declared to have committed ethical violations.